Kinin receptors in skin wound healing. Issue 2 (May 2016) - Soley, Bruna da Silva; Morais, Rafael Leite Tavares de; Pesquero, João Bosco; Bader, Michael; Otuki, Michel Fleith; Cabrini, Daniela Almeida
Highlights: We evaluated the involvement of kinins in skin healing process. Observe the influence of kinin in cellular infiltration into the damaged tissue. Check the involvement of kinin system in quality of tissue repair. We observed involvement of B2-kinin receptor in the proliferation of skin cells. Found involvement of B2-kinin receptor on the differentiation of myofibroblasts. Abstract: Background: Wound healing is a complex and dynamic process that includes 3 different phases: inflammation, proliferation, and remodeling. Kinins are vasoactive peptides released after tissue injury, and are directly involved in the development and maintenance of inflammatory processes, and their actions are mediated by the activation of receptors called B1 and B2 . Objective: We aimed to evaluate the involvement of kinin receptors in the skin healing process. Methods: Knockout mice for kinin receptors (KOB1, KOB2 and KOB1 B2 ) and wild type controls (WT) were subjected to a skin excision model, and tissue repair process was evaluated during different phases of wound healing. Results: In knockout animals for kinin receptors differences were observed in the resolution period of injury exceeding 17 days for the total closure of wounds. The absence of kinin receptors promotes a significant reduction in infiltration of polymorphonuclear cells on day 2 of the inflammatory phase. Already at the late stage of this phase (3 days) there was a negative influence on the infiltration of polymorphonuclear and mononuclear cells at the site of injury in comparison to WT. Collagen was significantly diminished in tissue of KOB1, KOB2 and KOB1 B2 from day two to the end of the healing process. Moreover, wound tissue from KOB2 and KOB1 B2, but not KOB1, presented impaired parameters of re-epitheliazation, reduced proliferation of cells (PCNA immunostaining), and a lower number of myofibroblasts (α-SMA immunostaining). Conclusion: These data reveal the involvement of kinin receptors in processes of skin repair. Both kinin receptors participate especially during the inflammatory phase, while B2 receptors seem to be more relevant in the quality of the wound scar. Thus, a better understanding of the contribution of kinins to skin wound healing may reveal novel options for therapy.